Análisis de la propuesta de Reglamento sobre los principios éticos para el desarrollo, el despliegue y el uso de la inteligencia artificial, la robótica y las tecnologías conexas - Lazcoz Moratinos, Guillermo (IUS ET SCIENTIA, 2020)
On 20 October 2020, the European Parliament adopted a resolution (2020/2012(INL)) with recommendations to the Commission regarding artificial intelligence, robotics and related technologies, which included a legislative proposal for a Regulation on the ethical principles for the development, deployment and use of these technologies. The content of this proposal undoubtedly follows from the regulatory vision that the European Commission has maintained in documents such as the White Paper on Artificial Intelligence (COM(2020) 65 final) or the Ethical guidelines for trustworthy AI drawn up by the High-Level Expert Group on AI. Given this new legislative horizon, it is more necessary than ever to address a constructive criticism on the proposal, highlighting the possibility of reformulating its markedly soft-law character despite its location in a regulatory source of general application and directly applicable, such as regulations, or the adopted approach for certain key principles such as human supervision or discrimination.